PSYCHOLINGUISTIC ANALYSIS OF NEWSPAPER ARTICLES IN ENGLISH MASS MEDIA - Aminboeva Shakhriniso Ulugbekovna (Research Focus International Scientific Journal, 2024)
This article is devoted to the psycholinguistic analysis of newspaper articles within the realm of English mass media. Language, being a powerful tool for communication, holds intricate nuances that influence cognition, perception, and behavior. Through employing psycholinguistic methodologies, this research aims to uncover patterns and mechanisms underlying the language used in newspaper articles. By examining lexical choice, syntactic structures, and discourse features, this study elucidates the psychological implications embedded within journalistic discourse. Insights garnered from this analysis contribute to a deeper understanding of how language shapes thought processes, attitudes, and societal perceptions.